Changing Paradigms, Subjects, and Approaches in Industrial Design Studio Education in Turkey - Filiz Yenilmez; H. Hümanur Bağlı (Anı Publishing, 2020)
Boundaries of industrial design discipline are expanding rapidly through new concepts that have emerged in recent years such as service design, experience design, sustainability, and social design. Additionally, the new approaches featuring co-design as collaboration and interdisciplinary approaches have started to take part in the agenda of design. In the framework of these developments, this study aims to discover subject and approach centered changes in industrial design studio education over the last twenty years. Accordingly, the compulsory design studio course, which is considered as the cornerstone of industrial design education, was defined as the research field and the semi-structured interview technique as a qualitative research method was used. As a result of the interviews carried out with the design educators, this research revealed the subject and approach oriented practices in industrial design studio courses within the context of changing interest areas of the design discipline.